Analisis Rasio Likuiditas, Solvabilitas dan Profitabilitas untuk Mengukur Kinerja Keuangan pada PT. Charoen Pokphand Indonesia Tbk Periode 2021-2025 - Aghnia Yasyfa; Anisa Roshy Rosdian; Hesti Hisani Latifah Hamdah; Megha Sakova (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the liquidity, solvency, and profitability ratios of PT Charoen Pokphand Indonesia Tbk (CPIN) during the 2021-2025 period to measure the company’s financial performance amid the fluctuating growth of Indonesia’s frozen food industry. The research employs a quantitative descriptive approach using secondary data obtained from the company’s annual financial statements published on the Indonesia Stock Exchange (IDX). Financial performance was assessed through eight ratios: Current Ratio, Cash Ratio, Quick Ratio, Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), each compared against industry standards. The results show that CPIN’s liquidity ratios—Current Ratio (average 1.60 times), Cash Ratio (24%), and Quick Ratio (1.2 times)—remain below industry standards and are categorized as unhealthy, although all three improved in 2024 and 2025. In contrast, the solvency ratios, DAR (30%) and DER (44%), are below industry thresholds, indicating a healthy and well-controlled debt structure. The profitability ratios also show healthy performance, with ROA averaging 34%, ROE 49%, and NPM 23%, all exceeding industry standards. Overall, CPIN’s financial condition during 2021-2025 is fairly sound, particularly in terms of solvency and profitability, while liquidity management still requires improvement to strengthen the company’s ability to meet its short-term obligations without compromising operational effectiveness.